Reading Aloud as a Language Intervention Strategy: A Case Study of Children with Functional Speech Delay at Rumah TIA Special Needs School in Sawahlunto City - Indah Mugianti; Damri; Antoni Tsaputra; Elsa Efrina; Rahmahtrisilvia (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
Functional speech delays affect children's communication skills, necessitating appropriate language intervention. This study aimed to examine the effectiveness of reading aloud in improving the speech skills of children with speech delays. A qualitative case study approach was used, involving five children at the Rumah TIA Special Needs School in Sawahlunto City. The intervention was delivered over four weeks, three times per week, with structured sessions tailored to each child's needs. Data were collected through observation, interviews, and documentation, and were analyzed thematically. The results showed increases in vocabulary mastery, pronunciation accuracy, and verbal participation following the intervention. All participants showed positive development, with variations influenced by age and initial conditions. These findings indicate that reading aloud is an effective and practical language intervention strategy. This activity is recommended for routine implementation in schools and homes as a fun method of language stimulation to support children's communication development. Keywords: reading aloud, speech delay, language intervention, child language development, case study